(3EPGYGJ GdEfJQfJ GdYQHjI h GdCLfHjI h GJLGgGJ GdTHGH GdYQHi fMhgG (B/ s - (3gHI MSf YdGA GdOjf eMeO TcQis; (3SGei GdTQja (B: s ((3GdbGgQI (B: s (3gHI MSf YdGA GdOjf eMeO TcQi (B: s, 2021)
(3JgOa gPg GdOQGSI Edi(B: (3JMOjO CfeGW JYQV GdTHGH GdYQHI dEPGYGJ GdEfJQfJ GdYQHjI h GdCLfHjI(B. (3JMOjO Cge EPGYGJ GdEfJQfJ GdYQHjI h GdCLfHjI GdJi jJYQV dgG GdTHGH GdYQHi(B. (3GdJYQa Ydi Cge OhGaY GdTHGH GdYQHi dGSJNOGe EPGYGJ GdEfJQfJ GdYQHjI h GdCLfHjI(B. (3bjGS GdJCKjQGJ GdeYQajI h GdhLOGfjI h GdSdhcjI dOi GdTHGH GdYQHi Mhd EPGYGJ GdEfJQfJ GdYQHjI h GdCLfHjI(B. (3QUO eOi GYJeGO GdTHGH GdYQHi Ydi EPGYGJ GdEfJQfJ GdYQHjI h GdCLfHjI ddMUhd Ydi GdeYdheGJ h GdehGO GdJQajgjI hbJ GdCReGJ(B. (3h GYJeOJ GdOQGSI ai EWGQgG GdfXQi Ydi fXQjI GdGYJeGO Ydi hSGFd GdEYdGe(B: (3h Je GSJNOGe efgL GdeSM h JWHjb GdOQGSI GdejOGfjI Ydi YjfI eJGMI JJchf ef (B400 (3eHMhK ai GdTHGH GdYQHi GdOQGSjI Ch Gdebjejf ai eUQ Ch eef Cecf GdhUhd Edjge ef NdGd THcI GdEfJQfJ(B. (3h CTGQJ fJGFL aQhV GdOQGSI Edi(B: (3KHJJ UMI GdaQV GdbGFd HhLhO aQhb PGJ OdGdI EMUGFjI ai cKGaI GdGSJeGY dEPGYGJ GdEfJQfJ GdYQHjI h GdCLfHjI h YGed GdfhY dUGdM GdPchQ h YGed GdLfSjI h gi GdLfSjI GdeUQjI(B. (3KHJ YOe UMI GdaQV GdbGFd HhLhO aQhb OdGdI EMUGFjI ai cKGaI GdGSJeGY dEPGYGJ GdEfJQfJ GdYQHjI h GdCLfHjI h GdeSJhi GdJYdjei h aFGJ GdYeQs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdOhd GdYQHjI (B- (3GdefXeI GdYQHjI ddJQHjI h GdKbGaI h GdYdhe (B- (3eYgO GdHMhK h GdOQGSGJ GdCaQjbjI (B- (3bSe GdHMhK h OQGSGJ GdEYdGes
(3UOQ GjVG cbQU eOeLs
Keywords: (3GJLGgGJ GdTHGH GdYQHis; (3EPGYGJ GdEfJQfJ GdCLfHjIs; (3EPGYGJ GdEfJQfJ GdYQHjIs